2018
DOI: 10.3389/fgene.2018.00008
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Karyotype Reorganization in the Fish Gymnotus arapaima (Gymnotiformes, Gymnotidae) Highlighted by Zoo-FISH Analysis

Abstract: The genus Gymnotus (Gymnotiformes) contains over 40 species of freshwater electric fishes exhibiting a wide distribution throughout Central and South America, and being particularly prevalent in the Amazon basin. Cytogenetics has been an important tool in the cytotaxonomy and elucidation of evolutionary processes in this genus, including the unraveling the variety of diploid chromosome number (2n = from 34 to 54), the high karyotype diversity among species with a shared diploid number, different sex chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…The similarities between the karyotype structures in Notopteridae species raise the question: are the chromosome pairs homeologous among these species? This question is pertinent to confirm chromosome markers in groups with much diversified karyotype evolution 70 , or to establish the conservation level of syntenic groups in those with much conserved karyotype macrostructure 21 . Thus, inter-specific cross-hybridization experiments using the painting probe XNI-1 derived from the first chromosome pair of X. nigri karyotype were performed to help to clarify this question.…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between the karyotype structures in Notopteridae species raise the question: are the chromosome pairs homeologous among these species? This question is pertinent to confirm chromosome markers in groups with much diversified karyotype evolution 70 , or to establish the conservation level of syntenic groups in those with much conserved karyotype macrostructure 21 . Thus, inter-specific cross-hybridization experiments using the painting probe XNI-1 derived from the first chromosome pair of X. nigri karyotype were performed to help to clarify this question.…”
Section: Discussionmentioning
confidence: 99%
“…Nagamachi et al (2010) produced whole chromosome probes (WCP) from G. c. orientalis (GCA42, 2n = 42, 30m/sm+12st/a) by flow sorting, and hybridized these probes to the cytotypes of G. c. orientalis with 2n = 40 (GCA40, 34m/sm+6st/a). Two other studies with WCP from GCA42 mapped the karyotypes of G. capanema (GCP 2n = 34, Nagamachi et al, 2013) and G. arapaima (GAR 2n = 44, Machado et al, 2018). Those studies showed a higher level of chromosomal rearrangement than previously thought between these species.…”
Section: Introductionmentioning
confidence: 82%
“…The results have helped to solve various issues in this field and have giving insights into several evolutionary issues (Barby et al, 2019). It has helped to bring insights into the origin of B chromosomes (Vicari et al, 2011;Scudeler et al, 2015;Utsunomia et al, 2016), the origin and evolution of sex chromosomes (Carvalho et al, 2017;Cioffi et al, 2017;de Oliveira et al, 2017;de Moraes et al, 2017;Yano et al, 2017;de Freitas et al, 2018) and helped in the understanding of chromosomal evolution and relationships between closely related species (Ráb et al, 2008;Nagamachi et al, 2010;Nagamachi et al, 2013;Milhomem et al, 2013;Machado et al, 2018;Cioffi et al, 2019). Nagamachi et al (2010) produced whole chromosome probes (WCP) from G. c. orientalis (GCA42, 2n = 42, 30m/sm+12st/a) by flow sorting, and hybridized these probes to the cytotypes of G. c. orientalis with 2n = 40 (GCA40, 34m/sm+6st/a).…”
Section: Introductionmentioning
confidence: 97%
“…The only option was to use pools of bacterial artificial chromosome (BAC) clones, which were found useful in plant species with small genomes (e.g., [ 44 , 45 ]). The development of oligo painting FISH [ 46 ] changed this situation dramatically, and it is now possible to label individual plant chromosomes and chromosomal regions in many species [ 47 , 48 , 49 , 50 , 51 , 52 ]. Chromosome-arm-specific oligo painting probes were also recently developed for banana ( Musa spp.)…”
Section: Discussionmentioning
confidence: 99%